Nivel de conocimiento de los padres de familia sobre la importancia de realizar el tamizaje neonatal a los recién nacidos en el Hospital Universitario de Motupe de la ciudad de Loja en el periodo comprendido de febrero - agosto 2016. - Romero Feijoó, Mayra Alejandra (2017)
The National Neonatal Screening Program is a fundamental public health instrument since it allows early diagnosis of congenital metabolic diseases and guide their management in a timely manner. This research was focused on determining the level of knowledge of the parents about the importance that has the Neonatal Screening Test, to assess the level of knowledge of health employees on the neonatal screening, as well as establish in which way the level of knowledge influences on health workers and parents. To carry out this research work a descriptive study was applied, using 10 questions survey focus toward health employees and parents, it was assigned one score: greater than 6 to a high level, from 4 to 6 medium and minor 4 low level. The sample was 50 parents and 15 surveys aimed at health employees. The results showed that 54 %(n=27) of parents who attend with their children to perform Neonatal Screening Test at “Motupe University Hospital” have a high level of knowledge, 30% (n = 15) a level of middling knowledge, while 16% (n = 8) has low level of knowledge. Regarding to health employees, it was gotten that 93.3% (n = 14) own a high level of knowledge, while in 6.7% (n = 1) of employees have an average level. Concerning to knowledge relationship among health workers it showed that it affects the level of knowledge of parents about Neonatal Screening since they provide information to parents. It is concluded that there was a high level of knowledge in both groups. Key words: knowledge, neonatal screening, parents, health employees